Sexual Orientation and Gender Identity Employment Discrimination - Green, Matthew William; Open Textbook Library (Open Textbook Library, 2017)
This Chapter will address the current protections that are available to lesbian, gay, bisexual and transgender ("LGBT") individuals who allege they have been victims of employment discrimination. The Chapter's primary focus will be on federal statutory law, particularly Title VII of the Civil Rights Act of 1964. Although the focus here is on federal law, Appendix I to this Chapter lists the states that protect individuals from public and/or private discrimination under state laws. This topic is explored in four parts: (1) a brief overview of congressional efforts to enact a statute to protect individuals from employment discrimination on the basis of sexual orientation and gender identity; (2) discusses Title VII and sexual orientation; (3) discusses ways in which recent courts have handled sexual orientation discrimination under Title VII; and (4) similarly examines early judicial treatment of claims brought by individuals alleging discrimination on the basis of their gender identity and/or expression and explores how the law has developed in this area as well.
I. Introduction -- II. A Federal Statute Protecting LGBT Employees -- III. Title VII and Sexual Orientation -- A. Early Judicial Perspectives -- B. The Evolving Meaning of "Discrimination Because of Sex" -- C. Stereotyping and Sexual Orientation -- D. Sexual Orientation Discrimination Is Sex Discrimination -- IV. Gender Identity and Expression -- A. Gender Identity and Expression and Sex Stereotyping -- B. An alternative route to protecting transgender employees
In English.
Description based on print resource
Keywords: Law -- Textbooks -- United States; Gender and Sexuality Studies -- Textbooks